Formulation of Admittance Control of a Surgical Robot About Remote Center of Motion - Dede, Mehmet İsmet Can; Balkan, M.A.; Dede, M.İ.C. (Springer Science and Business Media B.V., 2025)
Minimally invasive surgery procedures require the surgical tools to be moved about an incision point. Robots used for these surgeries must achieve this motion capability. When robots are used alongside the surgeon, additional considerations must be made regulating the surgeon-robot interaction. This paper presents a formulation of a compliance controller, namely an admittance controller, for use in the control of a surgical robot that is directed by physical interaction with the surgeon. The surgical robot in this study is a 6 degrees-of-freedom collaborative robot with a force/torque sensor attached to the distal end of its last joint. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2025.
International Federation for the Promotion of Mecha-nism and Machine Science (IFToMM)# University of Poitiers# the Grand Poitiers# the Nouvelle-Aquitaine region# the research project partner IRP-RACeS and the industrial partners Staubli and Mathworks#
Keywords: Admittance Controller; Remote Center Of Motion; Surgical Robots